2016
DOI: 10.1039/c5qo00281h
|View full text |Cite
|
Sign up to set email alerts
|

How easy is CO2 fixation by M–C bond containing complexes (M = Cu, Ni, Co, Rh, Ir)?

Abstract: A comparison between different M–C bonds (M = Cu(I), Ni(II), Co(I), Rh(I) and Ir(I)) has been reported by using density functional theory (DFT) calculations to explore the role of the metal in the fixation or incorporation of CO2 into such complexes. The systems investigated are various metal based congeners of the Ir-complex 8 [(cod)(IiPr)Ir-CCPh], with a ligand scaffold based on cod and IiPr ligands (cod = 1,5-cyclooctadiene; IiPr = 1,3-bis(isopropyl)imidazol-2-ylidene). The results of this study show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 81 publications
0
22
2
Order By: Relevance
“…It is not possible to conclude that one metal provides lowest barriers, however, it appears that Cu(I) generally gives feasible barriers, whereas Ni(II) may not be good for C-C bond formation with CO 2 [28,30,39]. All of the presented Cu-complexes use NHC ligands but as Lv et al indicated, other ligands, like e.g.…”
Section: Trendsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is not possible to conclude that one metal provides lowest barriers, however, it appears that Cu(I) generally gives feasible barriers, whereas Ni(II) may not be good for C-C bond formation with CO 2 [28,30,39]. All of the presented Cu-complexes use NHC ligands but as Lv et al indicated, other ligands, like e.g.…”
Section: Trendsmentioning
confidence: 99%
“…Based on the limited data for rhodium, insertion of CO 2 into a Rh-C sp bond involves no Rh-CO 2 interaction (Fig. 8) [28], as also observed for Cu. Insertion into Rh-C sp2 bonds occurs in a h 2 -fashion, where both C and O atoms coordinate to the metal Fig.…”
Section: Trendsmentioning
confidence: 99%
See 3 more Smart Citations